THE INFLUENCE OF NUMERIC ABILITY AND LEARNING MOTIVATION TOWARD STUDENTS’ MATHEMATICS LEARNING ACHIEVEMENT AT VII GRADE OF SMP MUHAMMADIYAH 1 MINGGIR SLEMAN - Laila Rahmawati; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The result of students’ mathematics learning achievement is influenced by many factors. Numerical ability and learning motivation are some factors expected to affect students’s achievement in learning mathematics. Therefore, this research was conducted in order to determine the effect of numerical ability and learning motivation toward students’ achievement in learning mathematics at SMP Muhammadiyah 1 Minggir, Sleman in the academic year 2016 / 2017. The research population was the seven grade students of SMP Muhammadiyah 1 Minggir, Sleman in the academic year 2016 / 2017, with the total of students are 212 students. The sample of this research is VII D and VII E as the experimental class and VII-A as an experimental class that determined non-random. The data collection technique using test and non-test technique.  Instrument items tested by using validity test,  discriminating power test and reliability test, while the questionnaire was tested by using reliability test and examined by experts. The data analysis used a hypothesis test. The result of the statistical hypothesis test found that on significance level 5% and the degree of freedom 56 shown that : (1) There is an influence of numerical ability towards mathematics learning achievement. It is shown in   and   so  , (2) There is an influence of learning motivation towards mathematics learning achievement. This is indicated by the value of  and  , so the value of  , (3) There is an influence of numerical ability and learning motivation towards mathematics learning achievement. This is shown by the value of   and  , so the value of  . The result of the statistical hypothesis test found that on significance level 5% and the degree of freedom 56 shown that : (1) mathematics learning achievement of a student who has a high numerical ability is better than student who has low numerical ability. It is proved by the value of  and   so  , (2) mathematics Learning achievement of a student who has a high learning motivation is better than a student who has low motivation. It the  in    and  , thus .